2015
DOI: 10.1086/682721
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Contact and Competition May Affect the Strength and Direction of Disease-Diversity Relationships for Directly Transmitted Microparasites

Abstract: The frequency of opportunities for transmission is key to the severity of directly transmitted disease outbreaks in multihost communities. Transmission opportunities for generalist microparasites often arise from competitive and trophic interactions. Additionally, contact heterogeneities within and between species either hinder or promote transmission. General theory incorporating competition and contact heterogeneities for disease-diversity relationships is underdeveloped. Here, we present a formal framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 45 publications
4
53
0
Order By: Relevance
“…Our analyses are broadly consistent with previous work (Begon et al, ; Bowers & Turner, ; Greenman & Hudson, , ; O'Regan et al, ; Strauss et al, ), showing that competition, parasitism and their relationships affect not only disease dynamics, but also the dynamics of host communities. We extend this thinking to include the effects of disease on community composition by exploring a wider range of ecological scenarios and by linking disease and community dynamics to specific traits (Figures and ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our analyses are broadly consistent with previous work (Begon et al, ; Bowers & Turner, ; Greenman & Hudson, , ; O'Regan et al, ; Strauss et al, ), showing that competition, parasitism and their relationships affect not only disease dynamics, but also the dynamics of host communities. We extend this thinking to include the effects of disease on community composition by exploring a wider range of ecological scenarios and by linking disease and community dynamics to specific traits (Figures and ).…”
Section: Discussionsupporting
confidence: 91%
“…Parasitism has, analogously to competition, been invoked as a force driving selection, population dynamics, community composition and food web dynamics (Dobson, Lafferty, & Kuris, ). Extensive theoretical work has shown that infectious disease can affect host communities and host coexistence outcomes (Greenman & Hudson, , ; Holt & Pickering, ; Joseph, Mihaljevic, Orlofske, & Paull, ; Mordecai, ; O'Regan, Vinson, & Park, ). For example, in a relatively simple system with two self‐regulating host species that share a parasite, various coexistence outcomes are possible, including the elimination of one host, or the coexistence of both hosts in the presence or absence of the parasite (Begon, Bowers, Kadianakis, & Hodgkinson, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations